The effect of experience quality on behavioral intentions mediated by tourist happiness and tourist satisfaction in an island destination - Sulfi Abdul Haji; Daud Hasim; Marwan Man Soleman; Karim Abubakar (Economics, Business, Accounting & Society Review, 2022)
This study aims to determine the influence of experience quality, tourist happiness, and tourist satisfaction on behavioral intentions. This study wanted to assess the role of tourist happiness and satisfaction in mediating experience quality's influence on behavioral intentions. This study used samples of domestic tourists who had experience traveling on the island of Dodola with a total of 210, with purposive sampling techniques with several predetermined criteria: 1. Have been 18 years old when filling out the questionnaire; 2. Have traveled on the island of Dodola; 3. At the same time, traveling on the island of Dodola. The data were analyzed using the Partial Least Square (PLS) technique with SmartPLS 3.0. the results showed that the variables of experience quality had a positive and significant effect on behavioral intentions, tourist happiness, and tourist satisfaction. Furthermore, tourist happiness and tourist satisfaction had a positive and significant impact on behavioral intentions. The influence of the quality of experience on the intention of behaving.